Analysis of Satisfaction the fast Food Restaurants using the C.45 Method in Medan - Dedi Andika Sihombing; Fahri Chairullah; Muhardi saputra; Nahla Naisylla Lubis; Palma Juanta (Sean Institute, 2022)
Analysis of customer satisfaction with fast food restaurants at one of the fast food restaurants, namely KFC in the city of Medan, is an interesting thing that the author wants to do. This restaurant has many branches. The city of Medan which consists of 21 sub-districts has at least 1 (one) KFC. With so many restaurants, there are various ratings expressed by the customer. Because there are slight differences between one another. when it comes to taste, there will be one voice for the consumers, but not on the price, facilities and services. However, there are also consumers who state that the taste is not good at one of the branches. Research data taken as many as 100 random consumers from different locations. The method used to analyze customer satisfaction is the c4.5 algorithm. The results obtained are the analysis of customer satisfaction which is the highest in taste at 64%. If it tastes good then the customer will feel very satisfied. If there is a bad taste, then the customer considers other things to make them feel satisfied with the fast food restaurant